ArtQuest: a virtual reality escape room for learning art history lessons / Nurin Farhana Zamil and Nor Intan Shafini Nasaruddin - Zamil, Nurin Farhana; Nasaruddin, Nor Intan Shafini (College of Computing, Informatics, and Mathematics, 2024)
The ArtQuest project bravely tackles the challenges associated with teaching art history, particularly in the context of Malaysia's "Pendidikan Seni Visual." Recognizing the prevalent issue of students finding art history dull due to uninspiring teaching methods, ArtQuest steps in as a game-changer. By harnessing the power of Virtual Reality (VR) technology, ArtQuest aims to inject excitement into the learning experience. The core objective revolves around making art history not only enjoyable but also enhancing students' ability to remember, understand deeply, and stay motivated. Executing a meticulous plan known as the ADDIE methodology, ADDIE is a step-by-step method ArtQuest used to create an engaging VR escape room, ensuring effective and enjoyable art history learning. ArtQuest brings forth a VR escape room that not only received a high satisfaction rate of 83.6% but also successfully blends fun with education. Looking forward, ArtQuest harbors aspirations to elevate its impact further. The plan involves collaboration with teachers to infuse additional captivating information into the VR experience, introducing more quizzes in each room to encourage users to test their knowledge about art history. This strategic move not only facilitates learning but also allows users to delve deeper into various art movements. ArtQuest also envisions supporting more languages, moving beyond Malay, to ensure inclusivity for a broader student base. Recognizing the dynamism of technology, ongoing updates to the VR technology remain a priority, as adding new features can enhance the overall learning experience. In essence, ArtQuest stands as a testament to successful innovation in education, and with future plans for enriching content, language support, and technological advancements, it aims to be an even more valuable and enjoyable educational tool for students preparing for the SPM exam in Malaysia.